The veterinary prescribing cascade: friend or foe?. (2nd September 2019) - Bowen, Mark
Abstract : Mark Bowen BVetMed MMedSci PhD DipACVIM DipECEIM DipECVSMR PFHEA FRCVS dispels some of the more common misconceptions